Comparative Study Between Seashore Power Plant and Power Plant Close to Factory to Supply Electrical Energy to Cement Plant in Pangkep Sulawesi Selatan - Anindito Wibisono, Ferry
Cement Plant is the one of energy intensive industries. Conservation effort is still required in order to reduce its energy consumption. One example of energy efficiency effort is optimizing the available thermal energy for drying raw material and coal before exhausting to the environment. An additional effort on optimization of electric energy consumption is constructing a private steam power plant that could also be combined with cement plant itself in order to increase utilization of thermal energy as high as possible. For a cement plant located not more than 15 km from seashore, two alternatives of power plant location, close to factory and seashore, are still interesting to be studied. Power plant constructed close to factory gives two advantages such as the opportunity of plant exhausted hot gas recovery for reducing thermal energy consumption and reduction on investment cost of power distribution equipment. However, it still has disadvantage on the high cost investment of cooling water piping system due to the distance that rather far from seashore. Contrary, power plant located seashore has lower investment cost on cooling water system and coal transportation cost. But it has higher investment cost on power distribution equipment and fuel consumption due to impossibility on recovering exhaust hot gas from the cement plant. This research is focused on the study of the evaluation of two above alternatives in point view technical and economic aspect. The study is limited for a cement plant with production capacity of around 7500 ton per day (tpd) which is located 14 km from seashore. The result of study show that power plant constructed close to factory gives more advantages on both technical and economic aspects. The reason is mainly due to higher thermal efficiency (36.7% compared to 33.63% for power plant located seashore) that impact on lower fuel consumption. The estimated difference profit gained per year between these two alternatives is around 2.965 billion IDR.